Characteristics and Efficiency of Heat Transfer for Natural Convection by Ag-CuO/H2O Hybrid Nanofluid Inside a Square Cavity with Corrugated Walls - Benderradji Razik; Brahimi Meryem; Gouidmi Hamza (Science, Engineering and Technology)
A parametric numerical study is conducted on laminar natural convection and heat transfer in a cavity with opposing undulated walls saturated with a hybrid Ag-CuO/water nanofluid. The two vertical walls of the sinusoidally undulated cavity are maintained at hot and cold temperatures, while the upper and lower walls are thermally insulated. The investigation examines the effects of relevant parameters such as the sinusoidally undulated geometry of the walls for different volumetric fractions of nanoparticles (0% ≤φ≤6%) and Rayleigh numbers (103 ≤ Ra ≤ 106) Thefinite-volumee discretization method is employed to solve the system of governing equations. The results indicate that an increase in the volumetric fraction of nanoparticles enhances the heat exchange rate in the cavity. Additionally, the Rayleigh number, with a significant increase in surface area, strongly influences the dominant heat transfer mode in the cavity. Furthermore, an increase in the number of wall undulations leads to a reduction in the heat transfer rate.